2020
DOI: 10.1016/j.jfluchem.2020.109630
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of complex unnatural fluorine-containing amino acids

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 167 publications
0
20
0
Order By: Relevance
“…On the basis of this successful as well as convenient proton shift process starting from the CF3-containing allylic alcohols 1, we envisaged its interesting extension from the synthetic point of view: thus, our idea was that the bisallylic ethers 2 possibly readily synthesized by way of the O-allylation of 1 were recognized as the potential substrates for the Claisen rearrangement as long as the proton shift of 3 to 4 was possible. It is worthwhile to note that, except for our previous report [9], there are no such examples to prepare the compounds 5 by way of Claisen rearrangement irrespective of the substituents R 2 , while there are some reports on the alkylation methods to alternatively get access to 5 [10][11][12][13]. We thus started our research for the novel utilization of the CF3-containing bisallylic ethers 3 as the potent substrates for the [3,3]-sigmatropic rearrangement via the facile isomerization to the corresponding allyl Scheme 1.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the basis of this successful as well as convenient proton shift process starting from the CF3-containing allylic alcohols 1, we envisaged its interesting extension from the synthetic point of view: thus, our idea was that the bisallylic ethers 2 possibly readily synthesized by way of the O-allylation of 1 were recognized as the potential substrates for the Claisen rearrangement as long as the proton shift of 3 to 4 was possible. It is worthwhile to note that, except for our previous report [9], there are no such examples to prepare the compounds 5 by way of Claisen rearrangement irrespective of the substituents R 2 , while there are some reports on the alkylation methods to alternatively get access to 5 [10][11][12][13]. We thus started our research for the novel utilization of the CF3-containing bisallylic ethers 3 as the potent substrates for the [3,3]-sigmatropic rearrangement via the facile isomerization to the corresponding allyl Scheme 1.…”
Section: Introductionmentioning
confidence: 91%
“…It is widely understood that strategic entry of fluorine atoms or fluorinated groups to adequate molecules gave strong impact to the original character in many instances, and thus development of novel methods for the construction of a variety of such compounds has attracted significant attention of researchers working in the field of synthetic organic chemistry, material science, and biologically active compounds [1][2][3][4][5]. For this reason, we have been studying to realize facile preparation of such molecules, and recently reported an interesting proton transfer starting from both propargylic [6] and allylic alcohols [7], enabling to form diverse ,-enones and saturated ketones, respectively, just by their treatment with very convenient as well as easy-to-handle tertiary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, peptides, especially short ones, can readily be prepared by well-established solid-phase methods, also for ease of purification [ 2 ]. Secondly, they allow greater chemical diversity, relative to other classes of compounds, which has been further expanded by the introduction of a large variety of non-natural amino acids [ 3 , 4 ]. Thirdly, as the complex function of proteins can be pinned to specific sets of peptide sequences, it has been shown that peptides can encode for at least some of protein functionalities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there exist a plethora of methods for the synthesis of FAAs, [19–23] however, the approaches for obtaining of PFAAs are still rare, especially in an enantioselective manner [24,25] . As a consequence, only several selective examples of asymmetric synthesis of PFAAs have been reported to date [26–33] .…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Moreover, the perfluoroalkylated AAs (PFAAs) are incorporated into peptides and proteins for their study and to modify and fine-tune their structures and physicochemical properties. [17,18] To date, there exist a plethora of methods for the synthesis of FAAs, [19][20][21][22][23] however, the approaches for obtaining of PFAAs are still rare, especially in an enantioselective manner. [24,25] As a consequence, only several selective examples of asymmetric synthesis of PFAAs have been reported to date.…”
Section: Introductionmentioning
confidence: 99%